Mangrove Fruits for Biofuel Production in Indonesia within the Framework of Climate Change Mitigation: A Literature Review of Technical and Policy Aspects - Mustofa, Ikrom; Nabilah, Rizka; Setyawan, Bagus Dwi (Open Science and Technology, 2025)
Aims: This study assesses the potential of mangrove fruits as a sustainable feedstock for biodiesel production to support climate change mitigation and adaptation in coastal regions.Methods: A peer-reviewed literature published between 2008 and 2025 was conducted to evaluate oil yield, fatty acid composition, and conversion challenges associated with mangrove-based biodiesel.Result: Quantitative findings show that several mangrove species exhibit exceptionally high oil content, notably Cerbera manghas Linn., with oil yields reaching 67.1%, significantly exceeding many conventional biodiesel feedstocks. Other promising species include Suaeda salsa (Linn.) Pall. (40%) and Wikstroemia indica (Linn.) (up to 39%). The extracted oils contain dominant fatty acids, palmitic, oleic, and linoleic acids, indicating strong compatibility with biodiesel standards. However, elevated free fatty acid (FFA) levels present technical constraints by reducing catalyst efficiency during transesterification, highlighting the need for pre-treatment or alternative catalytic approaches. From a policy perspective, mangrove-based biofuel development aligns with Indonesia’s National Energy Policy under Presidential Regulation No. 5 of 2006, which targets 5% biofuel use by 2025.Conclusion: Overall, mangrove fruits offer high technical potential, provided that processing, infrastructure, and policy support are strengthened.